Structural and statistical characterization of joints and multi-scale faults in an alternating sandstone and shale turbidite sequence at the Santa Susana Field Laboratory: Implications for their effects on groundwater flow and contaminant transport. (April 2016) - Cilona, Antonino; Aydin, Atilla; Likerman, Jeremias; Parker, Beth; Cherry, John
Abstract: This paper describes the properties of faults and fractures in the Upper Cretaceous Chatsworth Formation exposed at Santa Susana Field Laboratory and its surroundings (Simi Hills, California), where groundwater flow and contamination have been studied for over three decades. The complex depositional architecture of this turbidite consisting of alternating sandstones and shales, interacting with formative stress conditions are responsible for multi-scale fault hierarchies and permeable fractures in which nearly all groundwater flow occurs. Intensity and distribution of background fractures and their relation to bedding thickness are established for sandstones, the dominant lithology. The architecture of faults with increasing displacement is described, and relationships among fault dimensional parameters captured. Data from ∼400 boreholes and piezometers reveal the effect of faults and fractures on groundwater flow. Large hydraulic head differences, observed across fault zones with shale-rich cores, indicate these structures as cross-flow barriers. Moreover, hydraulic head profiles under ambient conditions, and pumping tests suggest strong hydraulic connectivity in all directions to depth of hundreds of meters. This outcrop-based structural characterization relates the horizontal hydraulic conductivity to the observed well-connected fracture network, and explains the strong vertical connectivity across low-hydraulic conductivity shales as faults and sheared fractures provide flow pathways. Graphical abstract: Highlights: Dimensional parameter of a fracture system were characterized for a turbidite sequence. Fault hierarchies depend on the thickness of the host stratigraphic intervals. Groundwater data reveal that faults with shale-rich cores impede cross-fault flow. The fractures classes providing pathways for contaminant movement were identified.